Kardiochirurgia dorosłychInfluence of hypertension on health-related quality of life in patients with acute coronary syndromes without ST-segment elevation assigned to coronary artery bypass graft surgery. Two-year follow-up - Szyguła-Jurkiewicz, Bożena; Trzeciak, Przemysław; Michalak, Alicja; Styn, Tomasz; Przybylski, Roman; Pacholewicz, Jerzy; Ryfiński, Bogusław; Foremny, Jerzy; Zembala, Marian; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Aim: The aim of the study was to compare 2-year health-related quality of life in patients with hypertension (group A) versus patients with normal blood pressure (group B) among 261 patients with acute coronary syndromes without ST-segment elevation who underwent early invasive strategy and coronary artery bypass grafting (CABG). Material and methods: The study group comprised patients with an episode of rest angina within 24 hours prior to admission who additionally fulfilled at least one of the following criteria: 1) ST-segment depression (≥0.5 mm) in at least 2 contiguous leads, 2) transient ( 0.1 ng/ml) or CK-MB (>5 ng/ml). All patients were sent Short Form (SF-36) health surveys 2 years after hospitalization. 240 (92%) completed the questionnaire. Group A comprised 157 patients whereas group B comprised 83 patients. Mental Component Summary Score (MCS) and Physical Component Summary Score (PCS) were compared between groups. Results: During the 2-year follow-up patients in group A more often required hospitalization (23 vs 10%, p <0.01), but percutaneous coronary interventions were less frequent in this group (0 vs 5%, p=0.03). The rate of unstable angina during follow-up was similar in both groups (5 vs 5%, NS). We found worse health-related quality of life in patients in group A regarding both Physical (41.51±10.61 vs 42.58±6.74, p<0.004) and Mental Component Summary (45.54±12.35 vs 48.95±9.9, p<0.03). Conclusion: The perception of mental and physical health obtained on the basis of patients’ subjective opinion 2 years after CABG surgery is worse in patients with concomitant hypertension.